Answer:
Answer: 241.6 ft² (Answer C)
Step-by-step explanation:
bisector of ZYXZ.
8
6.5
W
What is W Z?
Enter
your answer in the box. Do not round
your answer.
x
Z
6
units
Basic
Answer:
3.84 units
Step-by-step explanation:
By the properties of angle bisectors, ...
WZ/ZX = WY/YX
Solving for WY, we have ...
WY = (YX)(WZ)/(ZX) = (6.5/6)(WZ)
The length YZ is ...
YZ = 8 = WY +WZ
8 = (6.5/6)(WZ) +WZ = 12.5/6(WZ) . . . . substitute for WY
WZ = 8(6/12.5) . . . . multiply by 6/12.5
WZ = 3.84
Answer:
The correct answer is indeed 3.84 units
Step-by-step explanation:
I just took the test and got it correct hope this helps ☺
Answer:
x=4
Step-by-step explanation:
thats the answer ^^
Answer:
its the second one
Answer:
A. -0.87
Step-by-step explanation:
The correlation coefficient is a measure of the strength and nature of the linear relationship between two variables, one dependent and one independent. This coefficient takes values between -1 and 1, indicating with its sign whether the relationship is direct or inverse between the variables involved and with its absolute value indicates the strength of the linear relationship between them. A coefficient with absolute value close to 1 indicates great strength and better fit.
Conclusion: The best coefficient, of the propuetso in the problem, is that of -0.87, which indicates a strong relationship between the variables, a good fit and an inverse relationship between them.
B. y = (x + 3)2 – 6
C. y = (x + 2)2 – 6
D. y = (x + 2)2 – 3
The function that reveals the vertex of the parabola:is y = (x + 3)² - 6.
The general equation of a parabola is: y = a(x-h)² + k, where (h, k) indicates the vertex.
The given function is
y = x² + 6x + 3
⇒ y = (x² + 2 × x × 3 + 3²) - 6
⇒ y = (x + 3)² - 6
Therefore, the function y = (x + 3)² - 6 indicates the vertex of the parabola.
Learn more about parabola here:
#SPJ2
Answer:
B
Step-by-step explanation:
For the school work online
The value of is 2.
It is given that,
Explanation:
We have,
Substitute in the above function.
Thus, the value of is 2.
Learn more:
Answer:
h(0) is equal to 2.
Step-by-step explanation:
In order to find this, we first put 0 in for x in the g(x) equation.
g(x) = 2x - 1
g(0) = 2(0) - 1
g(0) = -1
Now that we have this, we can stick the answer for g(x) into the f(x) equation.
f(x) = 1 - g(x)
f(x) = 1 - -1
f(x) = 1 + 1
f(x) = 2
Answer:
$23.64
Step-by-step explanation:
12 * $1.97 = $23.64